Chronic C-Type Natriuretic Peptide Infusion Attenuates Angiotensin II-Induced Myocardial Superoxide Production and Cardiac Remodeling - Yasuhiro Izumiya; Satoshi Araki; Hiroki Usuku; Taku Rokutanda; Shinsuke Hanatani; Hisao Ogawa (International Journal of Vascular Medicine)
Myocardial oxidative stress and inflammation are key mechanisms in cardiovascular remodeling. C-type natriuretic peptide (CNP) is an endothelium-derived cardioprotective factor, although its effect on cardiac superoxide generation has not been investigated in vivo. This study tested the hypothesis that suppression of superoxide production contributes to the cardioprotective action of CNP. Angiotensin II (Ang II) or saline was continuously infused subcutaneously into mice using an osmotic minipump. Simultaneously with the initiation of Ang II treatment, mice were infused with CNP (0.05 μg/kg/min) or vehicle for 2 weeks. The heart weight to tibial length ratio was significantly increased by Ang II in vehicle-treated mice. Treatment with CNP decreased Ang II-induced cardiac hypertrophy without affecting systolic blood pressure. Echocardiography showed that CNP attenuated Ang II-induced increase in wall thickness, left ventricular dilatation, and decrease in fractional shortening. CNP reduced Ang II-induced increases in cardiomyocyte size and interstitial fibrosis and suppressed hypertrophic- and fibrosis-related gene expression. Finally, CNP decreased Ang II-induced cardiac superoxide production. These changes were accompanied by suppression of NOX4 gene expression. Our data indicate that treatment with CNP attenuated Ang II-induced cardiac hypertrophy, fibrosis, and contractile dysfunction which were accompanied by reduced cardiac superoxide production.